An analysis of Spatio-temporal variations of urban growth and impact of the dynamics of different class size cities in Assam, India - Poonam Sharma; Priyanka Tiwari (National Geographical Journal of India, 2022)
Urbanisation and urban growth have a direct effect on the development of the urban area at the town and city level. It also inuences the neighbouring areas by providing service to the buffer region. The urban growth pattern is majorly inuenced by population and economy. This study was conducted to identify and analyse the trend and spatial distribution, size class categories of urban population and its growth in Assam. Through analysis, it was conrmed that there exists a gap between the urban population in India and Assam. The gap has widened with 31% urban population in India and 14% urban population in Assam. There was more increase in numbers of Class V and VI towns and less number of Class I and II towns, contrary to this trend there has been more number of people residing in Class I and II towns. The urban structure has been analysed to show the relationship of class size, numbers and population share. Buffer analysis has been used to calculate the urban reach and inuence of different levels of urban centres.